(untitled) (Eurasian Journal of Humanities and Social Sciences, 2023)
Educational technology plays an important role in modernizing the teaching process in order to achieve effective learning, and to gain the most desirable educational results, especially in the light of some standards of technical enlightenment in the current era. This study aimed at evaluating the performance of Arabic language teachers at the intermediate stage in the light of some standards of technical enlightenment from the point of view of principals, by revealing the level of technical enlightenment among Arabic language teachers with its multiple dimensions such as the knowledge dimension and the skill dimension. The researcher adopted the analytical descriptive approach, and the research sample on the questionnaire was (28) male and female managers, and appropriate statistical methods were adopted to analyze the study data and obtain the results, the most important of which was that: Teachers’ commitment to the standards of the technical enlightenment scale was average in general, varying in its various dimensions The research ended with a conclusion that includes a brief and extensive presentation of the results it reached with a number of recommendations and suggestions. One of the most important recommendations of the research is the need for teachers of the Arabic language for the intermediate stage to be acquainted with the list of dimensions and paragraphs of technical enlightenment that were identified in this research with the aim of benefiting from them in teaching students and self-evaluation of their performance